Communication planning clean drug program at village level : (Case study of BNN Bantul Regency) - Anisa Sari, Eka; Wijanarko, Ari Wijanarko (COMMICAST, 2024)
Narcotics cases are complex problems related to legal, state security, health, economic and social issues. In 2022 Bantul Regency had 104 cases and became the second highest area prone to narcotics. In 2023 there was an increase to 129 cases. The drug-free village program aims to create a safe, comfortable, and peaceful situation in the village community. The study aims to find out the communication planning of the National Narcotics Board of Bantul Regency through Desa Bersinar (Drug-Free Village) in implementing the Drug Abuse Eradication and Illicit Trafficking Prevention program. This research uses an interpretive paradigm with a qualitative descriptive approach. Then the approach of the P-D-C-A (Plan-Do-Check-Action) stages of Strategic Management. The implementation of the shining village program has been running for 1 year, starting in January 2023. However, the implementation has not been optimal, such as budget planning for 2023 has not been budgeted, passive participation from the community in Shining Village activities, and the absence of effective communication between working groups, so that the use of communication media is still not optimal. The Plan and Do stages are very prominent, while the Check and Action stages are less prominent due to ineffective communication. A strategy is needed to develop all stages of effective communication. Then there is a need for additional outdoor communication media, such as pamphlets, posters, billboards, and banners at several points. As well as conducting Community-Based Intervention surveys every month so that evaluation and follow-up are running.